The characteristic differential spectrum of a conventional substitute signal source in machinery testing - CHOLEWA, Wojciech (Archives of Acoustics, 1976)
The paper concerns the evaluation of the acoustic signal which carries information on the dynamics of the interaction of machine elements. A method is presented which can be used for the experimental testing of machine character-istics by periodic excitation of the machine. The essence of this method is a new evaluation of the signal in the form of characteristic differential spectra which are dependent on the dynamics of the interaction of elements of the object to be tested and independent of the position of the microphone.